High-resolution structure of the alcohol dehydrogenase domain of the bifunctional bacterial enzyme AdhE - Liyana Azmi; Eilis C. Bragginton; Ian T. Cadby; Olwyn Byron; Andrew J. Roe; Andrew L. Lovering; Mads Gabrielsen (John Wiley and Sons Ltd, 2024)
Volume 76| Part 9| September 2020| Pages 414-421